Understanding party factionalism and fragmentation: The case of two Nkrumahist parties in Ghana. Issue 3 (3rd July 2022) - Boakye, Baffour Agyeman Prempeh
ABSTRACT: It is widely argued that intra-party struggles for leadership and the emergence of factions within any political party are inevitable. However, it becomes problematic when cooperative factionalism within political parties turns out to be degenerative. This article sets out to illuminate some possible triggers that have contributed to the inability for Ghana's Convention People's Party (CPP) and People's National Convention (PNC) to overcome their fragmentation. The argument here is that excessive personality cults, coupled with the exploitation of warring factions within the CPP and PNC, have undermined the electoral prospects of these two Nkrumahist-inspired parties. The article notes, among other dynamics, the need for these parties to build robust party structures, tone down on excessive personalisation of party leadership, and minimise political opportunism.